Analisis Kepatuhan Masyarakat terhadap Fatwa MUI No. 32/Kep/MUI-SU/VIII/2002 tentang Walimatul Ursy Keyboard Porno di Desa Sei Rotan (Islamika : Jurnal Ilmu-Ilmu Keislaman, 2026)
This study aims to analyze the socialization and level of community compliance with the Fatwa of Majelis Ulama Indonesia North Sumatra Number 32/Kep/MUI-SU/VIII/2002 concerning Attending Walimatul ‘Ursy Events Featuring Pornographic Keyboard Entertainment in Sei Rotan Village. The phenomenon of keyboard entertainment containing pornographic elements at wedding ceremonies is still frequently found in society, despite the issuance of the fatwa as a moral guideline for Muslims. This research employed a normative-empirical method with sociological, psychological, and legal approaches. The research was conducted as field research using purposive sampling techniques involving 10 informants consisting of religious leaders, community leaders, wedding hosts, and members of society who had attended walimatul ‘ursy events featuring keyboard entertainment. Data were collected through interviews, observation, and literature studies, then analyzed using descriptive qualitative analysis. The results showed that the dissemination of the fatwa in Sei Rotan Village has not been carried out optimally because its delivery is still limited to Friday sermons and religious gatherings, causing most people to lack a comprehensive understanding of the fatwa’s substance. The level of community compliance with the fatwa is relatively low due to limited religious knowledge, the strong influence of local entertainment culture, perceptions that the fatwa is not legally binding, and various social and economic factors. This study concludes that the low level of compliance is not caused by ideological rejection of Islamic teachings, but rather by weak dissemination efforts and the dominance of social-cultural practices within the community. Therefore, stronger synergy among religious scholars, local government, and community leaders is necessary to improve the dissemination of the fatwa in order to enhance legal awareness and shape more effective religious social behavior within society.